Rheological properties of frozen concentrated orange juice (FCOJ) as a function of concentration and subzero temperatures - Tavares, Denise Trigilio; Alcantara, Maria Regina; Tadini, Carmen Cecilia; Telis-Romero, Javier (Taylor & Francis Inc, 2007)
Data on flow properties of Frozen Concentrated Orange Juice (FCOJ) produced from oranges cv. Pera-Rio (65.04 Brix, 8.8% w/w pulp content, 2.5% w/w pectin, 3.84% citric acid, 1.293 g cm(-3)) from -18 to 0 degrees C were fitted with appropriate predictive models. The power law model was found to be the most appropriate to fit the flow curves obtained for FCOJ between 46.56 and 65.04 degrees Brix. In higher concentrations, thixotropy was observed and showed more temperature dependence. A single equation combining Arrhenius and exponential relationships was applied to describe the temperature effect and shear rate on the quantity of breakdown of FCOJ.
Keywords: frozen concentrated orange juice; rheological properties; thixotropic behavior; power law model